Pembuatan Program Aplikasi Untuk Analisis Persamaan Nonlinier Sine Gordon pada Long Josephson Junction Bahan Superkonduktor dengan Menggunakan Metode Finite Difference - Wellya Sari (PILLAR OF PHYSICS, 2013)
Josephson junction consists of two superconductor materials seperated by a thin isolator. Electricity current from juction can be explained by Sine-Gordon equation. From the equation, it will be obtained model of fluxon’s wave that is one of soliton. This research’s type is desriptive which use numerical approach by finite diffrence methode. It is designed a program that use Matlab R.2010 software to solve nonlinear equation and to get soliton’s solution.  From the solution,  fluxon and anti fluxon wave property on Long Josephson Junction can be analised. The solution show soliton characteristics, that a fluxon can move for long distance without any shape changed. If there is a fluxon  or antifluxon collision,  they will preserve ordinary shape.  When a fluxon reach end of junction, fluxon will be transformed to antifluxon, and vice versa. If current density jc is small then voltage is small too. Keywords:  Superconductors, Long Josephson Junction, fluxon